Avaliação da remoção de sulfametoxazol, diclofenaco e 17β-estradiol em água por meio de processo oxidativo com cloro - Souza, Brígida Prieto de [UNESP] (2014)
This study aimed to evaluate removing of sulphamethoxazole, diclofenac and 17β-estradiol on distilled and natural waters by oxidation with chlorine. The results indicated that the initial concentrations of microcontaminants as the inicial time, had a significant differences in both waters of study. For the tests in distilled water, high values of removing were found. The natural water was treated by clarification followed by post-chlorination and the results revealed that the best removal efficiency occurred for diclofenac then 17β-estradiol and sulphamethoxazole. In accordance with the Decree 2914/11, which establishes values of pH, temperature and contact time basis on the residual chlorine, the corresponding time would be up to 10 minutes for post-chlorination, so the best values were on the order of 61% for the DCF, 36% to E2 and 33% for SMX in distilled water, in addition, for natural waters, these values were 34% for the DCF to 24% to E2 and 11% for SMX. The doses of chlorine were compared and in distilled water only the DCF had a significant differences in the removal efficiency with the increase of the applied dose (3.0 mg l -1 ), but in the SMX and E2 no significant differences were observed. It was observed the formation of the sub products of chlorination described by other researchers with these microcontaminants in natural water for SMX and E2 in concentrations from 20 to 90 μg.L-1. However was not found the formation of sub products to DCF, which presented a major removal values found in this study. For the oxidation kinetics of the studied drugs, the ideal contact time was observed in 30 minutes for most studies and all microcontaminants has better adjustment to the kinetic model of the pseudo-second order, with K2 values in the order of 0.0133 (DCF), 0.0168 (SMX) and 0.0326 (E2) in distilled water and 0.0092 (DCF), 0.0025 (SMX) and 0.0479 (E2) in natural water